Community Adaption to Flood Hazards: A Case Study of Kg. Bekalau, Beaufort, Sabah, Malaysia: Adaptasi Masyarakat Terhadap Bahaya Banjir: Kajian Kes Kg. Bekalau, Beaufort, Sabah, Malaysia - Jafar, Adi; Sakke, Nordin; Mapa, Mohammad Tahir; Geogre, Fionna; Dinggai, Molia Sebi (GEOGRAFI, 2021)
The risk of encounter flood hazards increases as the population in floodplains grows. However, in order to continue to survive, communities in the floodplains, particularly in the Beaufort area, are implementing adaptation strategies in hopes of increasing resilience to disaster. Therefore, the objective of this study is to identify the adaptation strategies adopted by the residents of Beaufort floodplain and to assess the effectiveness of the adaptation strategy in reducing the risk of flood losses. Therefore, a total of 30 residents of Kg. Bekalau were used as samples for this study to answer the prepared questionnaire. The raw data obtained through the distribution of the questionnaires were then analysed descriptively using cross tabulation and frequency analysis. The analysis of the study revealed that the residents of Kg. Bekalau adopt various adaptation strategies to flood hazards such as building a stilt house (100%), owning a canoe (93%), building an attic (20%) and doorknobs (3.3%). Building stilt houses from three to 12 feet high can reduce the risk of economic loss, among other factors. The evidence is that during the largest flood tragedy, more than half (63.3%) of all respondents suffered only minor economic losses. The rest (36.6%) experienced no economic losses at all. Owning a canoe allows residents to better reach other areas during floods. More than half (53.3%) of respondents had no problem being stranded even though the flood was two metres high. The results of this study are very important as a source of information for stakeholders in strengthening disaster management, especially in flooded areas.